(untitled) (Journal of Contemporary Studies, 2017)
Abstract Media has crossed all boundaries in the age of satellite and digital telecast. With the rise of social media it has become impossible for even the most closed political systems to foster a particular direction to national discourse. However, there are countries using state-controlled electronic media to provide their version of information to their target audiences. Pakistan is one of them. Assessing the policy of Pakistan Television (PTV) and analysing the parameters of government control over dissemination of information is the focus of the paper. It also discusses how PTV manages to hold its central position amid a large number of private channels telecasting bold discussions on controversial subjects. In this regard, an important realisation is that there is a need of compromise between controlled media and people’s freedom of speech and information. It is concluded that Parliament’s oversight is imperative for ensuring a more public control with special focus on diversity and pluralism.